2002
DOI: 10.1364/ao.41.002650
|View full text |Cite
|
Sign up to set email alerts
|

Spin filtering with curve windows for interferometric fringe patterns

Abstract: Filtering off noise from fringe patterns is important for the processing and analysis of interferometric fringe patterns. Spin filters proposed by the author have been proven to be effective in filtering off noise without blurring and distortion to fringe patterns with small fringe curvature. But spin filters still have problems processing fringe patterns with large fringe curvature. We develop a new spin filtering with curve windows that is suitable for all kinds of fringe pattern regardless of fringe curvatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…To acquire the information of the profile of the measured element, the basic spin filter may be used to filter the noise in the interferograms [8]. In practice, it is found that the method sometimes fails to clear much noise in the smaller zone of the interference fringe patterns.…”
Section: The Measuring Principle and The Grid Line Methodsmentioning
confidence: 99%
“…To acquire the information of the profile of the measured element, the basic spin filter may be used to filter the noise in the interferograms [8]. In practice, it is found that the method sometimes fails to clear much noise in the smaller zone of the interference fringe patterns.…”
Section: The Measuring Principle and The Grid Line Methodsmentioning
confidence: 99%
“…The various low-pass filtering on the fringe contour will effectively filter the noise without the phase being damaged. The authors have proposed a series of fringe pattern processing methods employing the fringe orientation information, such as spin filter, 10 contoured-window filter, 11 etc., which have been applied successfully in the processing of various interferometric fringe patterns, including holography, moiré patterns, ESPI fringe patterns, etc., and the latest InSAR phase images. 12 The particularities of the fringe contour make many novel fringe processing methods possible.…”
Section: Defining Of the Contoured Window Of The Insar Phase Imagementioning
confidence: 99%
“…For fringe orientation, these mainly include the gradient-based method (GM) [5], the plane-fit method (PM) [6], and the fast Fourier transform method (FFTM) [7]. For fringe density, these mainly include the accumulate-differences method (ADM) [8], the continuous wavelet transform (CWT) [9], and the isotropic adaptive bandpass filter (IDBF) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The GM [5] is popularly used for its efficiency, but its accuracy can easily be lowered by speckle noise. The PM [6] can get accurate orientations in spite of high noise, but it is strict with the size of the calculating window. The FFTM [7] can give desired results of fringe orientation even in the regions with low or high fringe density and in noisy and poor contrast conditions, but it requires long computation times.…”
Section: Introductionmentioning
confidence: 99%